Biaxially oriented polyester film

A biaxially oriented polyester film with controlled microprotrusions and friction coefficients addresses adhesion and static mark issues, ensuring smooth secondary processing and improved gas barrier properties.

JP7619264B2Active Publication Date: 2025-01-22TOYOBO CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2021536834
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-07-31
Filing Date
2020-06-23
Publication Date
2025-01-22
Estimated Expiration
2040-06-23

Smart Images

  • Figure 0007619264000003
    Figure 0007619264000003
  • Figure 0007619264000004
    Figure 0007619264000004
  • Figure 0007619264000005
    Figure 0007619264000005
Patent Text Reader

Abstract

The present invention provides a biaxially oriented polyester film which has excellent transparency and is easy for secondary processing such as coating and vapor deposition, while achieving satisfactory performance after secondary processing. A biaxially oriented polyester film which is formed of a polyester resin composition containing particles, and which has at least one surface that satisfies all of the requirements (1) to (3) described below. (1) The number of fine projections having a height of less than 3 nm per an area of 4 × 10-12 m2 is from 250 to 600. (2) The number of fine projections having a height of not less than 3 nm per an area of 4 × 10-12 m2 is from 300 to 600. (3) The arithmetic mean height Sa is from 0.010 μm to 0.025 μm.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a biaxially oriented polyester film, and more particularly to a biaxially oriented polyester film suitable for secondary processing such as coating or deposition in order to further enhance the functionality of the biaxially oriented polyester film. [Background technology]

[0002] Conventionally, biaxially oriented polyester films have been widely used in a wide range of fields, such as packaging materials and industrial materials, due to their excellent mechanical strength, thermal properties, optical properties, etc. Although biaxially oriented polyester films have excellent oxygen barrier properties, in packaging applications for general food, retort food, pharmaceuticals, etc., there are increasing demands for design and oxygen barrier properties and water vapor barrier properties related to the alteration and deterioration of the contents, which can cause the alteration and deterioration of the contents.

[0003] For this reason, biaxially oriented polyester films used for packaging applications such as general food, retort food, and pharmaceuticals are being designed to further improve their adhesion to printing inks and their gas barrier properties against oxygen, water vapor, etc. For example, methods for improving the gas barrier property include laminating a film made of a resin with good gas barrier properties, such as polyvinylidene chloride or a polyethylene vinyl alcohol copolymer, onto a biaxially oriented polyester film, coating a liquid in which such a resin is dissolved and laminating a thin film, or depositing a metal such as aluminum or a metal oxide such as aluminum oxide onto the film surface to form a thin film.

[0004] In particular, vapor-deposited polyester films having a metal oxide on the film surface are widely used because they are excellent in terms of heat resistance and transparency in addition to gas barrier properties. However, it has not been easy to industrially and stably produce a vapor-deposited polyester film having a thin metal oxide film, such as a silicon oxide or aluminum oxide film, on its surface, which has good gas barrier properties.

[0005] Therefore, attempts have been made to improve the gas barrier properties of the vapor-deposited polyester film by controlling the surface condition of the biaxially oriented polyester film used as the substrate for the vapor-deposited polyester film, and proposals have been made to specify the center plane surface roughness and number of protrusions of the biaxially oriented polyester film (see, for example, Patent Document 1) and to specify the center line surface roughness of the biaxially oriented polyester film (see, for example, Patent Document 2).

[0006] Furthermore, a biaxially oriented polyester film has been proposed in which the number of fine protrusions having a specific height or more is controlled (see, for example, Patent Document 3).

[0007] Since these films control the state of the film with a focus only on improving the gas barrier property after the metal oxide thin film is provided, it cannot be said that there is sufficient improvement in the wrinkles in the film roll or adhesion of films in the film roll, i.e., blocking, when the film is wound into a film roll after the film is produced. Moreover, the performance after secondary processing such as coating and deposition is also not sufficient. [Prior art documents] [Patent documents]

[0008] [Patent Document 1] Japanese Patent Application Publication No. 10-119172 [Patent Document 2] Japanese Patent Application Publication No. 11-010725 [Patent Document 3] Patent No. 4834923 Summary of the Invention [Problem to be solved by the invention]

[0009] The object of the present invention is to overcome the problems of the conventional technology and to provide a biaxially oriented polyester film which is excellent in transparency, easy to perform secondary processing such as printing, coating and deposition, and has excellent properties after secondary processing. [Means for solving the problem]

[0010] The inventors investigated the causes of the deterioration of properties after secondary processing and found that, because biaxially oriented polyester film has electrical insulation properties, it is prone to static marks, which are areas that become locally charged due to contact with the transport rolls or peeling during the film production process or secondary processing process, and static mark discharge marks caused by the discharge of accumulated static electricity, and that it is difficult for the coated dissolved resin or evaporated inorganic oxide molecules to form a regular, uniform, and defect-free thin film on the film surface in these areas.

[0011] As a result of further intensive research by the inventors, it has been found that by setting the number of fine protrusions below a certain height on the film surface on the side where a coating film or vapor deposition film is formed to a specific number or more, it is possible to suppress the occurrence of locally highly charged areas and discharge marks known as static marks, as described above, and to improve performance after secondary processing, such as gas barrier properties, and that by setting the number of fine protrusions above a certain height and the shape of the protrusions within a specific range, it is possible to improve the slipperiness between films, and further that by setting the arithmetic mean height of the film surface within a specific range, transparency is less likely to decrease.

[0012] That is, the present invention comprises the following: 1. A biaxially oriented polyester film made of a polyester resin composition containing particles, at least one surface of which satisfies all of the following requirements (1) to (3): (1) Area 4×10 -12 m 2 The number of fine protrusions each having a height of less than 3 nm is 250 to 600. (2) Area 4×10 -12 m 2The number of fine protrusions having a height of 3 nm or more per unit area is 300 to 600. (3) The arithmetic mean height Sa is 0.010 μm or more and 0.025 μm or less.

[0013] 2. The biaxially oriented polyester film according to 1., wherein the coefficient of dynamic friction between the surface satisfying all of the requirements (1) to (3) and the opposite surface of the biaxially oriented polyester film is 0.20 or more and 0.60 or less.

[0014] 3. The biaxially oriented polyester film according to 1. or 2., wherein the surface of the biaxially oriented polyester film which satisfies all of the requirements (1) to (3) has a wetting tension of 50 mN / m or more.

[0015] 4. The biaxially oriented polyester film according to any one of 1. to 3., wherein the biaxially oriented polyester film has an external haze of 1.8% or less and an internal haze of 2.0% or less. Effect of the Invention

[0016] The present invention can provide a biaxially oriented polyester film that is excellent in transparency, is less likely to cause wrinkles in the film roll when wound into a film roll after the film is produced, and is easy to perform secondary processing such as coating or vapor deposition due to less adhesion between films in the film roll (so-called blocking phenomenon), and also has excellent performance after secondary processing.

[0017] In particular, in recent years, in order to increase the production efficiency of biaxially oriented polyester films, efforts have been made to increase the width and length of the biaxially oriented polyester film roll (hereinafter referred to as the master roll) that is first wound up after the stretching process. Even with such large film rolls, it is possible to obtain a biaxially oriented polyester film that has little wrinkling and blocking, is easy to perform secondary processing, and has satisfactory performance after secondary processing, such as the gas barrier properties of a vapor-deposited film. The same is true for film rolls that are made by slitting the master roll into smaller pieces. [Brief description of the drawings]

[0018] [Figure 1] A photograph of the film surface after it has been unwound from a film roll, where strongly charged areas are visualized using a charge distribution assessment toner.Static marks are observed. [Diagram 2] A photograph of the film surface after unwinding from a film roll, where the discharge marks on the surface have been visualized using a toner for assessing charge distribution.Static mark discharge marks are visible. [Diagram 3] Diagram showing the arrangement of biaxially oriented polyester film, film roll, anti-static brush, and meandering prevention device during unwinding DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0019] The present invention will be described in detail below. [Polyester resin composition] The biaxially oriented polyester film of the present invention is made of a polyester resin composition containing the following polyester resin as a main component. The polyester resin constituting the biaxially oriented polyester film of the present invention is a polymer synthesized from a dicarboxylic acid or its ester-forming derivative and a diol or its ester-forming derivative. Examples include polyethylene terephthalate, polybutylene terephthalate, and polyethylene-2,6-naphthalate, and polyethylene terephthalate is preferred from the viewpoints of mechanical properties, heat resistance, cost, etc. The term "main component" as used herein means that the content in the polyester resin composition is 80% by weight or more, preferably 90% by weight or more, more preferably 95% by weight or more, and most preferably 98% by weight or more.

[0020] In addition, these polyester resins may be copolymerized with other components as long as the object of the present invention is not impaired. Specifically, the copolymerization components include dicarboxylic acid components such as isophthalic acid, naphthalenedicarboxylic acid, 4,4-diphenyldicarboxylic acid, adipic acid, sebacic acid and their ester-forming derivatives. In addition, the diol components include diethylene glycol, hexamethylene glycol, neopentyl glycol, and cyclohexanedimethanol. In addition, polyoxyalkylene glycols such as polyethylene glycol and polypropylene glycol are also included. The copolymerization amount is preferably 10 mol% or less per constituent repeating unit, more preferably 5 mol% or less, and most preferably 3 mol% or less.

[0021] Examples of a method for producing the polyester resin that constitutes the biaxially oriented polyester film of the present invention include a method in which the above-mentioned dicarboxylic acid or its ester-forming derivative and the diol or its ester-forming derivative are used as main starting materials, and the polyester resin is then subjected to an esterification or ester exchange reaction in a conventional manner, followed by a polycondensation reaction at high temperature and reduced pressure.

[0022] The intrinsic viscosity of the polyester resin constituting the biaxially oriented polyester film of the present invention is preferably in the range of 0.50 to 0.90 dl / g, more preferably 0.55 to 0.80 dl / g, from the viewpoints of film formability and recollection.

[0023] In order to ensure that at least one surface of the biaxially oriented polyester film of the present invention satisfies all of the following requirements (1) to (3), it is preferable that the polyester resin composition of the present invention contains at least one type of particle selected from the group consisting of inorganic particles, organic particles, and particles consisting of a mixture thereof. (1) Area 4×10 -12 m 2 The number of fine protrusions each having a height of less than 3 nm is 250 to 600. (2) Area 4×10 -12 m 2The number of fine protrusions having a height of 3 nm or more per unit area is 300 to 600. (3) The arithmetic mean height Sa is 0.010 μm or more and 0.025 μm or less.

[0024] Examples of the inorganic particles used include particles made of silica (silicon oxide), alumina (aluminum oxide), titanium dioxide, calcium carbonate, kaolin, and barium sulfate. Examples of the organic particles include acrylic resin particles, melamine resin particles, silicone resin particles, and particles made of crosslinked polystyrene. Among these, particles made of silica (silicon oxide), calcium carbonate, or alumina (aluminum oxide), or particles made of polymethacrylate, polymethyl acrylate, or derivatives thereof are preferred, particles made of silica (silicon oxide) or calcium carbonate are more preferred, and inorganic particles made of silica (silicon oxide) are particularly preferred.

[0025] The particle size distribution of the particles used in the present invention is preferably monodisperse. The shape of the inorganic fine particles is not particularly limited, but the closer to a sphere the number of fine protrusions with a height of 3 nm or more can be increased without significantly changing the arithmetic mean height Sa, and the number of fine protrusions with a height of less than 3 nm can be increased.

[0026] The weight average particle size of the particles in the present invention, as measured with a Coulter counter, is preferably in the range of 0.8 to 1.8 μm. When the weight average particle size of the particles is 0.8 μm or more, the number of fine protrusions having a height of less than 3 nm and the arithmetic average height Sa tend to be equal to or greater than the lower limit values ​​of (1) and (3) above, respectively. When the weight average particle diameter of the particles is 1.8 μm or less, the arithmetic mean height Sa is easily controlled to be equal to or less than the upper limit value of (3) above, and it is also suitable for controlling the number of fine protrusions having a height of less than 3 nm to be equal to or more than the lower limit value of (1) above.

[0027] The lower limit of the particle content in the polyester resin composition in the present invention is preferably 1000 ppm by weight, more preferably 1300 ppm by weight, and particularly preferably 1400 ppm by weight. When the particle content is 1000 ppm by weight or more, the number of fine protrusions less than 3 nm in height and the number of fine protrusions 3 nm or more in height tend to be equal to or greater than the lower limit values ​​of (1) and (2) above, respectively. The upper limit of the particle content is preferably 3000 ppm by weight, more preferably 2500 ppm by weight, further preferably 2200 ppm by weight, and particularly preferably 1800 ppm by weight. When the particle content is 3000 ppm by weight or less, the number of fine protrusions less than 3 nm in height, the number of fine protrusions 3 nm or more in height, and the arithmetic mean height Sa are easily controlled to be equal to or less than the upper limit values ​​of (1), (2), and (3) above.

[0028] As a method for blending the particles in the polyester resin composition of the present invention, for example, the particles can be added at any stage of the esterification stage for producing the polyester resin, after the completion of the ester exchange reaction, or before the start of the polycondensation reaction. However, it is preferable to add the particles as a slurry dispersed in ethylene glycol or the like and then proceed with the polycondensation reaction. It is also preferable to use a method in which a slurry of particles dispersed in ethylene glycol or water or the like is blended with a polyester-based resin raw material using a vented kneading extruder, or a method in which dried particles are blended with a polyester-based resin raw material using a kneading extruder.

[0029] In the step of mixing the particles with the polyester-based resin raw material, it is preferable to minimize particle agglomerates in order to stably obtain the desired surface condition, but the influence of such agglomerates can be reduced by adjusting the conditions of the film-forming process of the biaxially oriented polyester film after the mixing step.

[0030] Furthermore, the polyester resin composition of the present invention may contain small amounts of other polymers, antioxidants, heat stabilizers, antistatic agents, ultraviolet absorbers, plasticizers, pigments, or other additives, within the scope of not impairing the object of the present invention.

[0031] [Manufacturing method of biaxially oriented polyester film] The biaxially oriented polyester film of the present invention can be obtained, for example, by melt-extruding a polyester resin composition containing the above-mentioned polyester resin as a main component with an extruder to form an unstretched sheet, and then stretching the unstretched sheet. Preferred examples are given below, but the present invention is not limited to these.

[0032] The biaxially oriented polyester film of the present invention may have a single layer, two layers, three layers, or a laminate structure of four or more layers. In the case of a two-layer structure or more, each layer is made of the polyester resin composition as described above, but it is preferable that the types or contents of the components of the polyester resin composition of adjacent layers are different. In the case of a two-layer structure, if the polyester resin compositions constituting each layer are represented as A and B, the structure can be, for example, A / A or A / B.

[0033] In the case of a three-layer or more structure, each layer is made of the polyester resin composition as described above, but it is preferable that the types or contents of the components of the polyester resin composition of adjacent layers are different. In the case of a three-layer structure, if the polyester resin compositions constituting each layer are represented as A, A', B, and C, the structure can be, for example, A / B / C, A / B / A, or A / B / A', but if there is no need to change the surface properties of both sides, it is easier to manufacture and preferable to have an A / B / A structure in which both layers are designed to have the same composition. Here, A, A', B, and C do not have the same composition.

[0034] In the case of a three-layer structure, even if there are no particles in the internal layers, the surface roughness of the film can be controlled by controlling the particle content only in the surface layer, and the particle content in the entire film can be reduced, which is preferable. This has the advantage of improving the problem of odor components escaping through voids (spaces) that form at the boundaries between the inorganic particles and the polyester resin, resulting in a decrease in fragrance retention. Furthermore, it is easy to use recycled materials from the edges generated during the film production process or recycled materials from other film production processes in the inner layer section, as long as it does not adversely affect the characteristics of the film surface, which is also advantageous in terms of cost.

[0035] When the polyester resin composition is melt-extruded, it is preferable to dry the polyester resin composition using a dryer such as a hopper dryer or a paddle dryer, or a vacuum dryer. After drying the polyester resin composition in this way, the polyester resin composition is melted at a temperature of 200 to 300°C, which is equal to or higher than the melting point of the polyester resin, and extruded into a film using an extruder. Alternatively, the polyester resin, particles, and additives as necessary may be sent out by separate extruders, merged, and then mixed and melted and extruded into a sheet. When extruding the molten resin composition, any existing method such as a T-die method or a tubular method can be used.

[0036] The sheet-like molten polyester resin composition after extrusion can be quenched to obtain an unstretched sheet. As a method for quenching the molten polyester resin composition, a method can be suitably adopted in which the molten polyester resin composition is cast onto a rotating drum from a die and quenched and solidified to obtain a substantially unoriented resin composition sheet. The temperature of the rotating drum is preferably set to 40° C. or lower.

[0037] Furthermore, the unstretched sheet obtained can be subjected to a combination of processes such as a longitudinal and transverse stretching process, a heat setting process, and a heat relaxation process as described below to obtain the biaxially oriented polyester film of the present invention. The details are explained below. The longitudinal direction means the direction in which the unstretched sheet runs, and the width direction means the direction perpendicular thereto.

[0038] The stretching method may be simultaneous biaxial stretching, in which stretching in the longitudinal direction and the width direction is performed simultaneously, or sequential biaxial stretching, in which stretching in either the longitudinal direction or the width direction is performed first. However, sequential biaxial stretching is most preferred from the viewpoints of a fast film-forming speed and high productivity, and of excellent thickness uniformity of the finally obtained biaxially oriented polyester film. The film-forming speed referred to here means the running speed (m / min) of the biaxially oriented polyester film when it is taken up around a master roll after the stretching step.

[0039] The temperature during stretching of the unstretched sheet in the longitudinal direction is preferably in the range of (Tg+15) to (Tg+55)°C, using the glass transition temperature (hereinafter, Tg) of the polyester resin as an index, and the stretch ratio is preferably in the range of 4.2 to 4.7 times. When the stretching temperature is (Tg+55)°C or lower and 4.2 times or higher, the number of fine protrusions less than 3 nm in height is easily increased to the lower limit of (1) or higher, the molecular orientation in the longitudinal direction and the width direction is well balanced, and the difference in physical properties between the longitudinal direction and the width direction is small, which is preferable. In addition, the flatness of the obtained biaxially stretched polyester film is also good, which is preferable. On the other hand, when the longitudinal stretching temperature is (Tg+15)°C or higher and the stretching ratio is 4.7 times or less, the arithmetic mean height Sa is easily controlled to be equal to or less than the upper limit of (3) above. This is preferable because the tensile stress (bowing phenomenon) generated in the direction opposite to the running direction of the film in the thermal relaxation step does not become too large.

[0040] In addition, in the longitudinal stretching, a method of stretching between a plurality of rolls in two, three, or four or more stages, rather than in one stage, is preferred because it allows the stretching ratio in the longitudinal direction to be increased without increasing the stretching speed too much, and therefore makes it possible to further reduce the difference in physical properties in the width direction of the film. Two-stage or three-stage stretching is preferred from the viewpoints of effect, equipment, and cost.

[0041] The film obtained by stretching the unstretched sheet in the longitudinal direction may be subjected to a surface treatment such as corona treatment or plasma treatment as necessary, and then a resin dispersion or resin solution may be applied to at least one surface of the film to impart functions such as easy slippage, easy adhesion, and antistatic properties.

[0042] When the film obtained by stretching an unstretched sheet in the longitudinal direction is to be stretched in the width direction, the film is introduced into a tenter device, both ends of the film obtained by stretching the unstretched sheet in the longitudinal direction are held with clips, and the film is heated to a predetermined temperature with hot air. After that, the film is transported in the longitudinal direction while the distance between the clips is increased, thereby stretching the film in the width direction. When the temperature during width direction stretching is Tg+5° C. or higher, the arithmetic mean height Sa is easily controlled to be equal to or less than the upper limit of the above (3), and breakage during stretching is less likely to occur, which is preferable. Furthermore, when the stretching temperature is Tg+40°C or lower, the number of fine protrusions having a height of less than 3 nm is easily set to be equal to or greater than the lower limit of (1) above, and uniform stretching in the width direction is facilitated, making it difficult for uneven thickness in the width direction to become large, which is preferable since it makes it difficult for the winding hardness of the film roll surface to vary greatly in the width direction. It is more preferably Tg+8°C or higher and Tg+37°C or lower, and even more preferably Tg+11°C or higher and Tg+34°C or lower. The stretching ratio in the width direction of the film obtained by stretching the unstretched sheet in the machine direction is preferably 4.0 times or more and 6 times or less. When the stretching ratio in the width direction is 4.0 times or more, the number of fine protrusions less than 3 nm in height is easily set to the lower limit value of (1) or more, a high yield is easily obtained in terms of material balance, and the mechanical strength is not decreased, thickness unevenness in the width direction is not likely to increase, and the winding hardness in the width direction of the film roll is not likely to vary, which is preferable. The stretching ratio in the width direction is more preferably 4.1 times or more, and even more preferably 4.2 times or more. Furthermore, when the stretching ratio in the transverse direction is 6 times or less, the arithmetic mean height Sa can be easily controlled to be equal to or less than the upper limit value of the above (3), and the film is less likely to break during stretching.

[0043] The widthwise stretching step is followed by a heat setting step. The heat setting temperature of the film obtained by stretching the unstretched sheet in the machine direction and then stretching the film in the width direction is preferably 240° C. or higher and 250° C. or lower. When the heat setting temperature is 240°C or higher, the number of fine protrusions less than 3 nm in height is easily made to be equal to or greater than the lower limit of (1) above, and the thermal shrinkage rate in both the longitudinal and transverse directions is not too high, which is preferable since it improves the thermal dimensional stability during vapor deposition processing. On the other hand, when the heat setting temperature is 250° C. or less, bowing is less likely to increase, which is preferable.

[0044] A heat relaxation treatment step is then carried out, which may be carried out separately from the heat setting step after the heat setting step, or may be carried out simultaneously with the heat setting step. The relaxation rate in the film width direction in the heat relaxation treatment step is preferably 4% or more and 8% or less. When the relaxation rate is 4% or more, the heat shrinkage rate in the width direction of the obtained biaxially stretched polyester film is not too high, and the dimensional stability during deposition processing is good, which is preferable. On the other hand, when the relaxation rate is 8% or less, the tensile stress (bowing phenomenon) generated in the opposite direction to the running direction of the film at the center of the film in the width direction does not become too large, and the rate of variation in the film thickness in the width direction does not become large, which is preferable.

[0045] In the heat relaxation treatment step, the film obtained by stretching the unstretched sheet in the longitudinal direction is stretched in the width direction, and during the time until the film is stretched in the width direction by heat relaxation, the restraining force in the width direction is reduced and the film slackens under its own weight. In addition, the film may expand due to the accompanying air currents of hot air blown out from nozzles installed above and below the film. As a result, the film is in a state in which it is very susceptible to vertical fluctuations, and the amount of change in the orientation angle and the oblique heat shrinkage difference of the obtained biaxially stretched polyester film is likely to vary greatly. Methods for reducing these problems include, for example, adjusting the speed of the hot air blown from the upper and lower nozzles to keep the film parallel.

[0046] The biaxially oriented polyester film for deposition of the present invention may be subjected to corona discharge treatment, glow discharge treatment, flame treatment, or surface roughening treatment, and may also be subjected to known anchor coat treatment, printing, decoration, etc., as long as the object of the present invention is not impaired.

[0047] [Characteristics of biaxially oriented polyester film] At least one surface of the biaxially oriented polyester film of the present invention preferably satisfies all of the following (1) to (3). Each of these will be described in detail. (1) Area 4×10 -12 m 2 The number of fine protrusions each having a height of less than 3 nm is 250 to 600. (2) Area 4×10 -12 m 2 The number of fine protrusions having a height of 3 nm or more per unit area is 300 to 600. (3) The arithmetic mean height Sa is 0.010 μm or more and 0.025 μm or less.

[0048] (1) Area 4×10 -12 m 2 Number of microprojections less than 3 nm per Since biaxially oriented polyester film has electrical insulation properties, static marks, which are areas that are partially charged due to contact with the transport roll or peeling during the film manufacturing and processing processes, and static marks caused by the discharge of stored static electricity, are prone to occur. -12 m 2 When the number of fine protrusions each having a height of less than 3 nm is 250 or more, static marks and static mark discharge marks are reduced, coating spots are less likely to occur after the coating layer is formed, the gas barrier performance of the formed inorganic thin film layer is improved, and performance after secondary processing is likely to be improved. The reason is that the area is 4 x 10 -12 m 2If the number of fine protrusions less than 3 nm in height per film is 250 or more, the film and the metal roll come into contact with each other with a strong force during the process of transporting and winding the produced film, and even if the high protrusions on the film surface are pressed in, the area of ​​contact between the film surface and the metal roll becomes extremely small, so the amount of charge due to friction is small, and as a result, it is thought that the number of static marks and static mark discharge marks is reduced. More preferably, the number is 300 or more, more preferably, 400 or more, and particularly preferably, 500 or more. This tendency also applies to the case of friction caused by contact between films. The number of fine protrusions less than 3 nm in height does not improve the slipperiness of the film or reduce its blocking properties, but has the characteristic that it is less likely to adversely affect the gas barrier properties of the inorganic thin film layer formed on the film surface. Furthermore, even if the number of fine protrusions less than 3 nm in height is in the range of 600 or less, the number of static marks and static mark discharge marks is sufficiently small.

[0049] (2) Area 4×10 -12 m 2 Number of microprojections with height of 3 nm or more per unit When the number of fine protrusions having a height of 3 nm or more is 300 or more, the coefficient of dynamic friction between the films does not become too small, and since the biaxially oriented polyester film has electrical insulation, it is possible to more effectively prevent static marks, which are areas partially charged due to contact with a transport roll or peeling during the film manufacturing process or processing process, and static mark discharge marks caused by the discharge of accumulated static electricity, etc. More preferably, the number is 400 or more, and even more preferably, 500 or more. If the number of fine protrusions having a height of 3 nm or more is 600 or less, the formed inorganic thin film layer can have sufficient gas barrier properties.

[0050] (3) Arithmetic mean height Sa If the arithmetic mean height Sa is 0.010 μm or more, adhesion (blocking phenomenon) between films and between films in the film roll at recesses between protrusions formed on the film surface is unlikely to occur, and secondary processing of the film can be smoothly performed, which is preferable. It is further preferably 0.013 μm or more, more preferably 0.017 μm or more, and particularly preferably 0.020 μm or more. When the arithmetic mean height Sa is 0.025 μm or less, the haze, especially the external haze, of the biaxially oriented polyester film is reduced, and the transparency is excellent, which is preferable, more preferably 0.023 μm or less, and even more preferably 0.020 μm or less. The arithmetic mean height Sa of the other film surface is also preferably in the same range.

[0051] (Kinematic friction coefficient) The dynamic friction coefficient between one surface of the biaxially oriented polyester film of the present invention and the opposite surface thereof is preferably 0.20 or more and 0.60 or less. If the ratio is 0.20 or more, the films do not slide too much against each other, and wrinkles are unlikely to occur in the film roll when the film roll is wound by a winder device during film production or slitting, and secondary processability is unlikely to decrease. It is more preferably 0.30 or more, and most preferably 0.35 or more. Furthermore, if the ratio is 0.60 or less, the films slide against each other, so that when the film roll is wound by a winder device during film production or slitting, the film roll is less likely to slip, and secondary processability is less likely to deteriorate. It is further preferably 0.50 or less, and most preferably 0.44 or less.

[0052] (Static friction coefficient) The static friction coefficient between one surface of the biaxially oriented polyester film of the present invention and the opposite surface thereof is preferably 0.20 or more and 0.60 or less. If the ratio is 0.20 or more, the films do not slide too much against each other, and wrinkles are unlikely to occur in the film roll when the film roll is wound by a winder device during film production or slitting, and secondary processability is unlikely to decrease. It is more preferably 0.30 or more, and most preferably 0.35 or more. Furthermore, when the film thickness is 0.60 or less, the films slide against each other, so that when the film roll is wound by a winder device during film production or slitting, the film roll is less likely to be misaligned, and secondary processability is less likely to deteriorate. It is further preferably 0.50 or less, particularly preferably 0.44 or less, and most preferably 0.40 or less.

[0053] (Maximum height Sz) The maximum height Sz of the surface of the biaxially oriented polyester film of the present invention that satisfies all of the above (1) to (3) is preferably 0.5 μm or more and 2.0 μm or less. If the maximum height Sz is 0.5 μm or more, the amount of air trapped between the films in contact with each other when winding the master roll or when slitting the master roll and winding the biaxially oriented polyester film onto the core is less likely to increase, resulting in less stretching and deformation of the film. In addition, the film in the roll is less likely to sag after the air in the film roll is released. If the weight average particle size of the particles contained in the polyester resin is 0.8 μm or more, it is easy to make the maximum height Sz 0.5 μm or more. When the maximum height Sz is 2.0 μm or less, the biaxially oriented polyester film tends to have fewer defects such as missing coat films and inorganic thin film layers after secondary processing. When the temperature during longitudinal stretching is Tg+40° C. or less or the stretch ratio is 4.2 times or more, the maximum height Sz is easily made 2.0 μm or less. The maximum height Sz of the other film surface is similar.

[0054] (External Haze) The external haze of the biaxially oriented polyester film of the present invention is preferably 1.8% or less. If the external haze is 1.8% or less, the smoothness of the film surface is not easily impaired, charging is not easily caused by contact with the transport roll or peeling during the film production process, and quality defects due to charging such as static marks and static mark discharge marks are not easily caused. It is further preferably 1.6% or less, more preferably 1.4% or less, particularly preferably 1.2% or less, and most preferably 1.0% or less.

[0055] (Internal Haze) The internal haze of the biaxially oriented polyester film of the present invention is preferably 2.5% or less. If the internal haze is 2.5% or less, the transparency is less likely to decrease, which is preferable. It is further preferably 2.0% or less, more preferably 1.8% or less, and particularly preferably 1.6% or less.

[0056] (Wetting tension) One surface of the biaxially oriented polyester film of the present invention may be subjected to surface modification by a surface treatment such as low-temperature plasma treatment or corona discharge treatment. In this case, the wetting tension of the surface of the biaxially oriented polyester film of the present invention that satisfies all of the above (1) to (3) is preferably 50 mN / m or more, more preferably 52 mN / m or more. There is no particular upper limit, but even if it is in the range of 55 mN / m or less, the performance after secondary processing coating or evaporated thin film is sufficient.

[0057] (film thickness) The film thickness of the biaxially oriented polyester film of the present invention is preferably 5 to 40 μm. If it is 5 μm or more, the strength and stiffness of the film will not decrease, and the film roll is less likely to wrinkle when wound by a winder device, which is preferable. On the other hand, if the film thickness is in the range of 40 μm or less, sufficient strength and stiffness can be obtained, and it is preferable to make the film thinner from the viewpoint of cost. The film thickness is more preferably 8 to 30 μm, and particularly preferably 9 to 20 μm.

[0058] (Deposition film) A gas barrier layer, such as an inorganic thin film layer or a metal foil such as aluminum foil, can be provided on at least one surface of the biaxially oriented polyester film of the present invention that satisfies all of the following (1) to (3). (1) Area 4×10 -12 m 2 The number of fine protrusions each having a height of less than 3 nm is 250 to 600. (2) Area 4×10 -12 m 2 The number of fine protrusions having a height of 3 nm or more per unit area is 300 to 600. (3) The arithmetic mean height Sa is 0.010 μm or more and 0.025 μm or less.

[0059] The inorganic thin film layer is a thin film made of a metal or an inorganic oxide. There are no particular limitations on the material forming the inorganic thin film layer as long as it can be made into a thin film, but from the viewpoint of gas barrier properties, inorganic oxides such as silicon oxide (silica), aluminum oxide (alumina), and a mixture of silicon oxide and aluminum oxide are preferred. In particular, a composite oxide of silicon oxide and aluminum oxide is preferred from the viewpoints of compatibility between flexibility and denseness of the thin film layer and transparency.

[0060] In the composite oxide of silicon oxide and aluminum oxide, the mixing ratio of silicon oxide and aluminum oxide is preferably in the range of 20 to 70% Al by weight of the metal content. If the Al concentration is less than 20%, the water vapor gas barrier property may be reduced. On the other hand, if it exceeds 70%, the inorganic thin film layer tends to become hard, and there is a risk that the film will be destroyed during secondary processing such as printing or lamination, resulting in a decrease in gas barrier property. Note that silicon oxide here refers to various silicon oxides such as SiO and SiO2 or mixtures thereof, and aluminum oxide refers to various aluminum oxides such as AlO and Al2O3 or mixtures thereof.

[0061] The inorganic thin film layer has a thickness of usually 1 to 100 nm, preferably 5 to 50 nm. If the inorganic thin film layer has a thickness of less than 1 nm, it may be difficult to obtain satisfactory gas barrier properties, while if the inorganic thin film layer has a thickness exceeding 100 nm, the corresponding improvement in gas barrier properties cannot be obtained, and it is rather disadvantageous in terms of flex resistance and production costs.

[0062] The method for forming the inorganic thin film layer is not particularly limited, and any known deposition method such as physical deposition methods (PVD methods) such as vacuum deposition, sputtering, and ion plating, or chemical deposition (CVD) may be appropriately adopted. A typical method for forming the inorganic thin film layer will be described below using a silicon oxide-aluminum oxide thin film as an example. For example, when the vacuum deposition method is adopted, a mixture of SiO2 and Al2O3, or a mixture of SiO2 and Al, is preferably used as the deposition raw material. Particles are usually used as these deposition raw materials, and in this case, it is desirable that the size of each particle is large enough that the pressure during deposition does not change, and the preferred particle diameter is 1 mm to 5 mm. Heating can be performed by resistance heating, high-frequency induction heating, electron beam heating, laser heating, or other methods. It is also possible to introduce oxygen, nitrogen, hydrogen, argon, carbon dioxide, water vapor, or other reactive gases as reaction gases, or to adopt reactive deposition using means such as ozone addition and ion assist. Furthermore, the film formation conditions can be changed arbitrarily, such as applying a bias to the deposition target (laminated film to be subjected to deposition), or heating or cooling the deposition target. The deposition material, reactive gas, bias of the deposition target, heating / cooling, etc. can be changed in the same manner when the sputtering method or CVD method is adopted. Furthermore, a print layer may be laminated on the inorganic thin film layer.

[0063] In the present invention, it is preferable to provide a protective layer on the gas barrier layer. The gas barrier layer made of a metal oxide is not a completely dense film, but has minute defects scattered therein. By forming a protective layer by applying a specific resin composition for protective layer described later on the metal oxide layer, the resin in the resin composition for protective layer penetrates into the defective parts of the metal oxide layer, resulting in an effect of stabilizing the gas barrier properties. In addition, by using a material having gas barrier properties for the protective layer itself, the gas barrier performance of the laminated film is also greatly improved.

[0064] Examples of the protective layer include resins such as urethane-based, polyester-based, acrylic-based, titanium-based, isocyanate-based, imine-based, and polybutadiene-based resins to which curing agents such as epoxy-based, isocyanate-based, and melamine-based curing agents have been added. Examples of the solvent (solvent) used when forming the protective layer include aromatic solvents such as benzene and toluene; alcohol-based solvents such as methanol and ethanol; ketone-based solvents such as acetone and methyl ethyl ketone; ester-based solvents such as ethyl acetate and butyl acetate; and polyhydric alcohol derivatives such as ethylene glycol monomethyl ether.

[0065] The above-mentioned urethane resin is preferred because the polar group of the urethane bond interacts with the inorganic thin film layer and also has flexibility due to the presence of amorphous portions, so that damage to the inorganic thin film layer can be suppressed even when a bending load is applied. The acid value of the urethane resin is preferably within the range of 10 to 60 mgKOH / g, more preferably within the range of 15 to 55 mgKOH / g, and even more preferably within the range of 20 to 50 mgKOH / g. When the acid value of the urethane resin is within the above range, the liquid stability is improved when the resin is made into an aqueous dispersion, and the protective layer can be uniformly deposited on the highly polar inorganic thin film, resulting in a good coat appearance.

[0066] The urethane resin preferably has a glass transition temperature (Tg) of 80° C. or higher, more preferably 90° C. or higher. By making the Tg 80° C. or higher, it is possible to reduce swelling of the protective layer due to molecular motion during the moist heat treatment process (heating-heating-cooling). From the viewpoint of improving the gas barrier property, it is more preferable to use a urethane resin containing an aromatic or araliphatic diisocyanate component as a main constituent component as the urethane resin. Among these, it is particularly preferable to contain a metaxylylene diisocyanate component. By using the above resin, the cohesive strength of the urethane bond can be further increased due to the stacking effect between aromatic rings, and as a result, good gas barrier properties can be obtained. In the present invention, the ratio of aromatic or araliphatic diisocyanate in the urethane resin is preferably in the range of 50 mol% or more (50 to 100 mol%) in 100 mol% of the polyisocyanate component (F). The total amount of aromatic or araliphatic diisocyanate is preferably 60 to 100 mol%, more preferably 70 to 100 mol%, and even more preferably 80 to 100 mol%. As such a resin, the "Takelac (registered trademark) WPB" series commercially available from Mitsui Chemicals, Inc. can be suitably used. If the total amount of aromatic or araliphatic diisocyanate is less than 50 mol%, good gas barrier properties may not be obtained.

[0067] The urethane resin preferably has a carboxylic acid group (carboxyl group) from the viewpoint of improving the affinity with the inorganic thin film layer. In order to introduce a carboxylic acid (salt) group into the urethane resin, for example, a polyol compound having a carboxylic acid group, such as dimethylolpropionic acid or dimethylolbutanoic acid, may be introduced as a copolymerization component as a polyol component. In addition, after synthesizing the urethane resin containing a carboxylic acid group, the urethane resin in a water dispersion can be obtained by neutralizing it with a salt forming agent. Specific examples of the salt forming agent include ammonia, trialkylamines such as trimethylamine, triethylamine, triisopropylamine, tri-n-propylamine, and tri-n-butylamine, N-alkylmorpholines such as N-methylmorpholine and N-ethylmorpholine, and N-dialkylalkanolamines such as N-dimethylethanolamine and N-diethylethanolamine. These may be used alone or in combination of two or more.

[0068] (Laminate) The biaxially oriented polyester film of the present invention may be used as a substrate film and a layer of another material may be laminated thereon to form a laminate. As a method for this, the biaxially oriented polyester film may be laminated after production or during film formation.

[0069] For example, the biaxially oriented polyester film of the present invention, or a biaxially oriented polyester film of the present invention provided with an inorganic vapor deposition layer, can be further coated with a heat-sealable resin layer called a sealant and used as a packaging material. The heat-sealable resin layer is usually formed by extrusion lamination or dry lamination. The thermoplastic polymer forming the heat-sealable resin layer may be any polymer capable of sufficiently exhibiting sealant adhesiveness, and examples of such polymers include polyethylene resins such as HDPE, LDPE, and LLDPE, polypropylene resins, ethylene-vinyl acetate copolymers, ethylene-α-olefin random copolymers, and ionomer resins.

[0070] The sealant layer may be a single layer film or a multilayer film, and may be selected according to the required function. For example, in order to provide moisture resistance, a multilayer film containing a resin such as an ethylene-cyclic olefin copolymer or polymethylpentene may be used. In addition, the sealant layer may contain various additives such as a flame retardant, a slip agent, an antiblocking agent, an antioxidant, a light stabilizer, and a tackifier. The thickness of the sealant layer is preferably from 10 to 100 μm, and more preferably from 20 to 60 μm.

[0071] Examples of layer configurations of a laminate for a packaging material using the biaxially oriented polyester film of the present invention as a base film include base film / gas barrier layer / protective layer, base film / gas barrier layer / protective layer / adhesive layer / sealant layer, base film / gas barrier layer / protective layer / adhesive layer / resin layer / adhesive layer / sealant layer, base film / adhesive layer / resin layer / gas barrier layer / protective layer / adhesive layer / sealant layer, base film / gas barrier layer / protective layer / printed layer / adhesive layer / sealant layer, and base film / printed layer / gas barrier layer / protective layer / adhesive layer. Examples include adhesive layer / sealant layer, base film / gas barrier layer / protective layer / adhesive layer / resin layer / printing layer / adhesive layer / sealant layer, base film / adhesive layer / resin layer / printing layer / gas barrier layer / protective layer / adhesive layer / sealant layer, base film / printing layer / gas barrier layer / protective layer / adhesive layer / resin layer / adhesive layer / sealant layer, base film / printing layer / adhesive layer / resin layer / gas barrier layer / protective layer / adhesive layer / sealant layer, base film ...printing layer / adhesive layer / sealant layer, and the like.

[0072] The laminate using the biaxially oriented polyester film of the present invention can be suitably used for applications such as packaging products, various label materials, lid materials, sheet molded products, laminated tubes, etc. In particular, it is used for packaging bags (for example, pillow bags, standing pouches, four-sided pouches, and other pouches). The thickness of the laminate can be appropriately determined depending on the application. For example, it is used in the form of a film or sheet having a thickness of about 5 to 500 μm, preferably about 10 to 300 μm. EXAMPLES

[0073] The present invention will be described in more detail below with reference to examples. However, the present invention is not limited to the embodiments of the examples, and can be modified as appropriate without departing from the spirit of the present invention.

[0074] A. The evaluation method for polyester resin is as follows. [Glass transition temperature (Tg)] Using a differential scanning calorimeter (DSC6220, manufactured by SII NanoTechnology Inc.), 5 mg of the resin sample was melted to 280°C under a nitrogen atmosphere, held for 5 minutes, and then rapidly cooled with liquid nitrogen. Measurements were performed at a heating rate of 20°C / min from room temperature.

[0075] [Intrinsic viscosity (IV)] 0.2 g of polyester resin was dissolved in 50 ml of a mixed solvent of phenol / 1,1,2,2-tetrachloroethane (60 / 40 (weight ratio)), and the viscosity was measured using an Ostwald viscometer at 30° C. The unit is dl / g.

[0076] B. The polyester film was evaluated as follows. [Film thickness] The measurement was performed using a dial gauge in accordance with JIS K7130-1999 Method A.

[0077] [External haze, internal haze, total haze] A piece measuring 5 cm in length and 5 cm in width was cut out from the obtained film, and the total haze was measured for all wavelengths of visible light at 25° C. in accordance with JIS-K7136 using a turbidity meter (NDH5000) manufactured by Nippon Denshoku Industries Co., Ltd. Similarly, the haze of a laminate having only Zedel oil sandwiched between two quartz glass plates (hereinafter referred to as "haze H1") and the haze of a laminate having a polyester film whose surface was uniformly wetted with Zedel oil sandwiched between two quartz glass plates (hereinafter referred to as "haze H2") were measured. Next, the internal haze is calculated according to the following formula. Internal haze = haze(H2)-haze(H1) Equation 1 The external haze is determined by subtracting the internal haze from the total haze. The total haze, internal haze, and external haze all refer to the haze for all wavelengths of visible light.

[0078] [Arithmetic mean height roughness Sa, maximum height Sz] The obtained film was cut into an area of ​​10 cm length x 10 cm width, and scanned using a Zygo white laser interferometer (NEW VIEW8300) under the following observation conditions to measure the arithmetic mean height (μm) and maximum height (μm). The measurement was performed on the surface excluding foreign matter such as unmelted material and dust. Measurements were taken at 10 randomly selected points on a 10 cm x 10 cm sample, and the average values ​​were taken as the arithmetic mean height Sa and the maximum height Sz, respectively. (Observation conditions) Objective lens: 10x Zoom lens: 1x Field of view: 0.82 x 0.82 mm Sampling interval: 0.803μm Estimated measurement time: 4 seconds Type: Surface Mode: CSI Z resolution: High Scan length: 20μm Camera mode: 1024×1024@100Hz Shutter speed: 100% Light output: 1.3% Option: SureScan Off SmartPsi Averages 4 Noise Reduction Signal processing option: Fringe order analysis Advanced Fringe removal ON

[0079] [Kinematic friction coefficient, static friction coefficient,] The obtained film was cut into a piece measuring 400 mm in the longitudinal direction and 100 mm in the transverse direction to prepare a sample film. This was aged for 12 hours in an atmosphere of 23°C and 65% RH, and then divided into a test piece measuring 300 mm in the longitudinal direction and 100 mm in the transverse direction for the test table and a test piece measuring 100 mm in the longitudinal direction and 100 mm in the transverse direction for the sliding piece. The test piece for the test table was set on the test table, and the test piece for the sliding piece was the bottom surface (area size 39.7 mm2) of a metal sliding piece with a load of 1.5 kg. 2The pieces were attached to a rectangular plate (square) with double-sided tape so that the surfaces that had been in contact with the casting drum faced each other. The sliding speed of the test piece was 200 mm / min, 23° C., and 65% RH, and the other conditions were in accordance with JIS K-7125. The dynamic friction coefficient and static friction coefficient were each measured, and the average of three measurements was used.

[0080] [Film surface area 4×10 -12 m 2 Number of micro-projections in A piece measuring 10 mm in the longitudinal direction and 10 mm in the transverse direction was cut out from the obtained film, and measured under the following observation conditions using a scanning probe microscope (SPM-9700) manufactured by Shimadzu Corporation, and an image of the measurement surface was captured. The obtained images (height traces) were subjected to image processing under the following conditions. Using the SPM-9700 series particle analysis software, the threshold value of particles to be extracted under the following particle analysis conditions was set to 3 nm, and the number of particles 3 nm or larger and particles smaller than 3 nm were counted on an area of ​​4 × 10 -12 m 2 The counting was performed within a 2 μm x 2 μm square area. The measurement was carried out five times at different locations, and the number of fine protrusions was calculated by averaging the three measurements excluding the highest and lowest counts. (Observation conditions) Cantilever: Made of silicon (Si) Scanning mode: Phase mode Scanning speed: 2Hz Scanning range: 2μm Resolution: 256 x 256 Offset X: 0μm Offset Y: 0μm Scan angle: 0° Operating point: 1.0V P-Gain: 0.001 I-Gain: 1500 Offset Z: 0μm Z range: x2 Scanning mode: constant force (Image Processing) Tilt correction: average value in X direction (X), average value in Y direction (Y), line fit (L) Noise line removal: Mode (range specification), Auto selection (particle analysis) Target Shape: Particle XY Threshold: 30% Number of pixels to ignore: 5

[0081] [Friction charging voltage] The obtained film was cut into a piece measuring 80 mm in the longitudinal direction and 50 mm in the transverse direction to prepare a sample film. This was aged for 16 hours in an atmosphere of 23°C and 50% RH. The frictional charging voltage was measured using a frictional charging voltage measuring instrument (RST-300a) manufactured by Daiei Scientific Instruments Co., Ltd. The test sample was fixed to a rotating device and rubbed against a metal plate for 60 seconds at a drum rotation speed of 400 rpm, and the static electricity generated was measured, and the maximum value was taken as the frictional charging voltage. The measured frictional charging voltage was evaluated according to the following criteria. ◎: Frictional charge voltage less than 200V ○: Frictional charging voltage 200V or more, less than 500V △: Frictional charge voltage 500V or more, less than 1000V ×: Frictional charging voltage 1000V or more

[0082] [Static Mark Evaluation] The obtained biaxially oriented polyester film roll was wound to a width of 550 mm and a length of 500 m, and was rewound using a Nishimura Manufacturing Co., Ltd. slitter (FN105E type) at a speed of 15 m / min and a winding tension of 100 N / m (unit tension setting). To remove static electricity at this time, the static electricity removal device attached to the slitter was turned on and static electricity removal brushes (Achilles Corporation's "NSP-2S") were placed on the top and bottom sides of the film between the unwinding roll and the tilt adjustment roller to remove static electricity. The film was unwound from the outermost edge of the obtained film roll, and 2 m was removed from the edge, after which the film was sampled at a length of 10 cm from the center in the width direction and 10 cm in the length direction, and the charge state of the film surface was visualized using a charge distribution judgment toner manufactured by Kasuga Electric Co., Ltd. The charge property of the film roll was evaluated according to the following criteria. ⊚: No static marks, static mark discharge marks or toner adhesion. ◯: No static marks or static mark discharge marks were observed, but toner was attached. ×: Static marks or static mark discharge marks are observed.

[0083] [Wetting tension] A piece measuring 400 mm in the longitudinal direction and 300 mm in the transverse direction was cut out from the obtained film, and after aging for 24 hours at a temperature of 23°C and a relative humidity of 50%, the corona-treated surface was measured according to the following procedure in accordance with JIS-K-7100, except that the test atmosphere was a temperature of 23°C and a relative humidity of 50%. Place the test specimen on the hand coater substrate, place a few drops of the test mixture on the specimen, and immediately spread it by pulling the wire bar. If a cotton swab or brush is used to spread the test mixture, the liquid should be at least 6 cm 2 Spread the liquid quickly over the above area. The amount of liquid should be enough to form a thin layer without creating any puddles. The wetting tension is judged by observing the liquid film of the test mixture in a bright place and checking the state of the liquid film after 3 seconds. If the liquid film does not break and remains in the same state as when it was applied for 3 seconds or more, it is considered to be wet. If the wetting persists for more than 3 seconds, proceed to the mixture with the next highest surface tension. Conversely, if the liquid film breaks in 3 seconds or less, proceed to the next mixed liquid with a lower surface tension. Repeat this process to select a mixed liquid that can accurately wet the surface of the test piece in 3 seconds. Use a new swab for each test. Brushes or wire burs should be cleaned with methanol and dried after each use, as residual liquids will change composition and surface tension upon evaporation. The procedure is repeated at least three times to select the mixture that can wet the corona-treated surface in 3 seconds, and the surface tension of the mixture thus selected is reported as the wetting tension of the film.

[0084] [Example 1] The raw materials used were a resin composition for the surface layer (A) in which amorphous silica particles with an average particle size of 1.7 μm and polyethylene terephthalate (intrinsic viscosity = 0.62 dl / g, Tg = 78°C) were mixed to give a particle content of 2400 ppm by weight, and a resin composition for the base layer (B) in which silica with an average particle size of 1.3 μm and polyethylene terephthalate (intrinsic viscosity (IV) = 0.62 dl / g, Tg = 78°C) were mixed to give a particle content of 400 ppm by weight. Using two melt extruders, the raw resins were dried, and the mixed resin forming the surface layer (A) was melt-extruded from the first extruder at a resin temperature of 285°C, and the mixed resin forming the base layer (B) was melted from the second extruder at a resin temperature of 285°C, and the layers were laminated in a T-die in the order of surface layer (A) / base layer (B) / surface layer (A) from the side contacting the casting drum so that the thickness ratio was 1 / 10 / 1 (μm), extruded from a T-shaped die, and cooled and solidified on a casting drum with a surface temperature of 35°C to obtain an unstretched polyethylene terephthalate sheet. At that time, static electricity was applied using a wire-shaped electrode with a diameter of 0.15 mm, and the sheet was brought into close contact with the cooling drum to obtain a three-layer unstretched film. The obtained unstretched film was heated to 115°C and stretched in the longitudinal direction at a total stretch ratio of 4.5 times in three stages, 1.24 times in the first stage, 1.4 times in the second stage, and 2.6 times in the third stage. The film was then stretched in the width direction at a temperature of 140°C and a stretch ratio of 4.3 times, heat-set at 245°C, and heat-relaxed by 5% in the width direction. The surface of layer A in contact with the chill roll was then heated at 40 W·min / m 2 A biaxially oriented polyester film having a thickness of 12 μm was obtained, and the film was wound up to a width of 550 mm and a length of 500 m in the longitudinal direction. The raw material composition and film formation conditions of the obtained film are shown in Table 1. The physical properties and evaluation results of the obtained film are shown in Table 2. The film was evaluated on the surface of layer A that had been in contact with the chill roll.

[0085] [Example 2] Except for changing the silica particles as the raw material to amorphous silica particles having an average particle size of 1.3 μm and changing the silica particle content to 2000 ppm by weight, a biaxially stretched film was produced in the same manner as in Example 1 to obtain a biaxially oriented polyester film having a thickness of 12 μm. The physical properties and evaluation results of the obtained film are shown in Table 2.

[0086] [Example 3] A biaxially stretched film was produced in the same manner as in Example 1, except that the silica particles used as the raw material were changed to amorphous silica particles with an average particle size of 1.3 μm and the silica particle content was changed to 1500 ppm by weight, to obtain a biaxially oriented polyester film having a thickness of 12 μm. The physical properties and evaluation results of the obtained film are shown in Table 2.

[0087] [Example 4] The raw materials used were a resin composition for the surface layer (A) in which amorphous silica particles with an average particle size of 1.3 μm and polyethylene terephthalate (intrinsic viscosity = 0.62 dl / g, Tg = 78°C) were mixed to give a silica particle content of 1500 ppm by weight, and a resin composition for the base layer (B) in which silica with an average particle size of 1.3 μm and polyethylene terephthalate (intrinsic viscosity = 0.62 dl / g, Tg = 78°C) were mixed to give a particle content of 400 ppm by weight. Using two melt extruders, after drying each raw material resin, the first extruder melt extrudes the mixed resin forming the surface layer (A) at a resin temperature of 285 ° C., and the second extruder melts the mixed resin forming the base layer (B) at a resin temperature of 285 ° C., and the layers are laminated in the order of surface layer (A) / base layer (B) / surface layer (A) from the chill roll contact side so that the thickness ratio is 1 / 10 / 1 (μm) in a T-die, extruded from a T-shaped die, cooled and solidified on a casting drum, and an unstretched polyethylene terephthalate sheet was obtained. At that time, static electricity was applied using a wire-shaped electrode with a diameter of 0.15 mm, and the film was adhered to the cooling drum to obtain a three-layer unstretched film. The resulting unstretched film was heated to 115° C. and stretched in the machine direction at a total stretch ratio of 4.5 times in one stage. Subsequently, the film was stretched in the width direction at a temperature of 140°C and a stretch ratio of 4.5 times, heat-set at 245°C, and subjected to a 5% thermal relaxation treatment in the width direction to obtain a biaxially oriented polyester film with a film thickness of 12 μm, which was then wound up to a length of 550 mm in the width direction and 500 m in the longitudinal direction. The surface A layer used in the film evaluation was the surface that had been in contact with the chill roll. The raw material composition and film formation conditions of the obtained film are shown in Table 1. The physical properties and evaluation results of the obtained film are shown in Table 2. The film was evaluated on the surface of layer A that had been in contact with the chill roll.

[0088] [Example 5] A biaxially stretched film was produced in the same manner as in Example 3, except that the silica particles used as the raw material were changed to spherical silica particles having an average particle size of 1.3 μm, to obtain a biaxially oriented polyester film having a thickness of 12 μm. The physical properties and evaluation results of the obtained film are shown in Table 2.

[0089] [Example 6] A biaxially stretched film was produced in the same manner as in Example 3, except that the silica particles used as the raw material were changed to spherical silica particles having an average particle size of 1.0 μm, to obtain a biaxially oriented polyester film having a thickness of 12 μm. The physical properties and evaluation results of the obtained film are shown in Table 2.

[0090] [Example 7] Except for changing the silica particles as the raw material to spherical silica particles having an average particle size of 1.0 μm and changing the silica particle content to 1200 ppm by weight, a biaxially stretched film was produced in the same manner as in Example 1 to obtain a biaxially oriented polyester film having a thickness of 12 μm. The physical properties and evaluation results of the obtained film are shown in Table 2.

[0091] [Example 8] A biaxially stretched film was produced in the same manner as in Example 3, except that the silica particles used as the raw material were changed to amorphous silica particles having an average particle size of 0.8 μm, to obtain a biaxially oriented polyester film having a thickness of 12 μm.

[0092] [Comparative Example 1] Except for changing the silica particles as the raw material to amorphous silica particles having an average particle size of 2.7 μm and changing the silica particle content to 1500 ppm by weight, a biaxially stretched film was produced in the same manner as in Example 1 to obtain a biaxially oriented polyester film having a thickness of 12 μm. The physical properties and evaluation results of the obtained film are shown in Table 2.

[0093] [Comparative Example 2] Except for changing the silica particles as the raw material to amorphous silica particles having an average particle size of 2.4 μm and changing the silica particle content to 1500 ppm by weight, a biaxially stretched film was produced in the same manner as in Example 1 to obtain a biaxially oriented polyester film having a thickness of 12 μm. The physical properties and evaluation results of the obtained film are shown in Table 2.

[0094] [Comparative Example 3] The raw materials used were a resin composition in which amorphous silica particles with an average particle size of 1.3 μm and polyethylene terephthalate (intrinsic viscosity = 0.62 dl / g, Tg = 78°C) were mixed to give a silica particle content of 1500 weight percent ppm for the surface layer (A), and a resin composition in which silica polyethylene terephthalate with an average particle size of 1.3 μm (intrinsic viscosity = 0.62 dl / g, Tg = 78°C) was mixed to give a particle content of 400 weight percent ppm for the base layer (B). Using two melt extruders, after drying each raw material resin, the first extruder melt extrudes the mixed resin forming the surface layer (A) at a resin temperature of 285 ° C., and the second extruder melts the mixed resin forming the base layer (B) at a resin temperature of 285 ° C., and the layers are laminated in the order of surface layer (A) / base layer (B) / surface layer (A) from the chill roll contact side so that the thickness ratio is 1 / 10 / 1 (μm) in a T-die, extruded from a T-shaped die, cooled and solidified on a casting drum, and an unstretched polyethylene terephthalate sheet was obtained. At that time, static electricity was applied using a wire-shaped electrode with a diameter of 0.15 mm, and the film was adhered to the cooling drum to obtain a three-layer unstretched film. The obtained unstretched film was heated to 115°C and stretched in the longitudinal direction at a total stretch ratio of 4.0 times in three stages, 1.24 times in the first stage, 1.4 times in the second stage, and 2.3 times in the third stage. Subsequently, the film was stretched in the width direction at a temperature of 105°C and a stretch ratio of 4.0 times, heat-set at 235°C, and subjected to a 5% thermal relaxation treatment in the width direction to obtain a biaxially oriented polyester film with a film thickness of 12 μm, which was then wound up to a length of 550 mm in the width direction and 500 m in the longitudinal direction. The surface A layer used in the film evaluation was the surface that had been in contact with the chill roll. The raw material composition and film formation conditions of the obtained film are shown in Table 1. The physical properties and evaluation results of the obtained film are shown in Table 2. The film was evaluated on the surface of layer A that had been in contact with the chill roll.

[0095] [Comparative Example 4] Except for changing the silica particles as the raw material to amorphous silica particles having an average particle size of 1.3 μm and changing the silica particle content to 900 ppm by weight, a biaxially stretched film was produced in the same manner as in Example 1 to obtain a biaxially oriented polyester film having a thickness of 12 μm. The physical properties and evaluation results of the obtained film are shown in Table 2.

[0096] [Comparative Example 5] Except for changing the silica particles as the raw material to amorphous silica particles having an average particle size of 1.3 μm and changing the silica particle content to 5000 ppm by weight, a biaxially stretched film was produced in the same manner as in Example 1 to obtain a biaxially oriented polyester film having a thickness of 12 μm. The physical properties and evaluation results of the obtained film are shown in Table 2.

[0097] [Comparative Example 6] Except for changing the silica particles as the raw material to spherical silica particles having an average particle size of 0.5 μm and changing the silica particle content to 1500 ppm by weight, a biaxially stretched film was produced in the same manner as in Example 1 to obtain a biaxially oriented polyester film having a thickness of 12 μm. The physical properties and evaluation results of the obtained film are shown in Table 2.

[0098] As shown in the results of Table 2, the films of Examples 1 to 8 had the number of fine protrusions 3 nm or more in height, the number of fine protrusions less than 3 nm in height, and the arithmetic mean height Sa within the specified range, and therefore had few quality defects due to static marks and static mark discharge marks and other electrostatic defects, and therefore had excellent performance after secondary processing such as coating and vapor deposition.

[0099] In Comparative Example 1, the number of fine protrusions having a height of 3 nm or more of the obtained film was within the specified range, but the number of fine protrusions having a height of less than 3 nm was small, so that the frictional electrification voltage was high and the static mark evaluation was poor. Moreover, since the arithmetic mean height Sa was too large, the external haze was large and the transparency was poor.

[0100] In Comparative Example 2, the number of fine protrusions having a height of 3 nm or more of the obtained film was within the specified range, but the number of fine protrusions having a height of less than 3 nm was small, so that the frictional electrification voltage was high and the static mark evaluation was poor. Moreover, since the arithmetic mean height Sa was too large, the external haze was large and the transparency was poor.

[0101] In Comparative Example 3, the number of fine protrusions having a height of 3 nm or more and the arithmetic mean height Sa of the obtained film were within the range, but the number of fine protrusions having a height of less than 3 nm was small, so the frictional charging voltage was high and the static mark evaluation was poor.

[0102] In Comparative Example 4, the number of fine protrusions having a height of 3 nm or more and the number of fine protrusions having a height of less than 3 nm were too small for the obtained film, so that the frictional electrification voltage was high and the static mark evaluation was poor.

[0103] In Comparative Example 5, the number of fine protrusions with a height of 3 nm or more, the number of fine protrusions with a height of less than 3 nm, and the maximum height Sz of the obtained film were within the range, but the arithmetic mean height Sa was too large, so the external haze was large and the transparency was poor.

[0104] In Comparative Example 6, the number of fine protrusions having a height of 3 nm or more was within the range for the obtained film, but the number of fine protrusions having a height of less than 3 nm was low, so that the frictional electrification voltage was high and the static mark evaluation was poor. [Industrial Applicability]

[0105] The biaxially oriented polyester film of the present invention has excellent transparency, is less likely to cause wrinkles in the film roll during film production or when wound onto a film roll after slitting, and is easy to unwind from the film roll, making it easy to perform secondary processing such as coating and vapor deposition. In addition, since there are few quality defects caused by static marks and static mark discharge marks, etc., due to charging, the performance after secondary processing such as coating and deposition is excellent. Therefore, it is useful for food packaging applications, particularly for applications to films with gas barrier properties, and is expected to make a significant contribution to the industrial world.

[0106] [Table 1]

[0107] [Table 2]

Claims

1. A biaxially oriented polyester film made of a polyester resin composition containing particles, the particle content in the polyester resin composition being 2500 ppm by weight or less, and at least one surface of the biaxially oriented polyester film satisfying all of the following requirements (1) to (3): (1) Area 4×10 -12 m 2 The number of fine protrusions each having a height of less than 3 nm is 250 or more and 600 or less per one. (2) Area 4×10 -12 m 2 The number of fine protrusions having a height of 3 nm or more per one particle is 300 to 600. (3) The arithmetic mean height Sa is 0.01 μm or more and 0.023 μm or less.

2. 2. The biaxially oriented polyester film according to claim 1, wherein the coefficient of dynamic friction between the surface satisfying all of the requirements (1) to (3) and the opposite surface of the biaxially oriented polyester film is 0.20 or more and 0.60 or less.

3. 3. The biaxially oriented polyester film according to claim 1, wherein the surface of the biaxially oriented polyester film that satisfies all of the requirements (1) to (3) has a wetting tension of 50 mN / m or more.

4. 3. The biaxially oriented polyester film according to claim 1, wherein the biaxially oriented polyester film has an external haze of 1.8% or less and an internal haze of 2% or less.

5. 3. The biaxially oriented polyester film according to claim 1, wherein the thickness of the biaxially oriented polyester film is from 5 μm to 40 μm.

Citation Information

Patent Citations

  • Preparation method of biaxially oriented polyester film for electronics tapes

    CN106142794A

  • JP1973034923A

  • Polyester film for electrophotography

    JP1992060644A

  • Vapor deposited biaxially oriented polyester film

    JP1998119172A

  • Polyester film for transparent deposition

    JP1999010725A